Forward Position Solution of 3-RPS in-Parallel Manipulator Based on Particle Swarm Optimization - Hong Li Zhang; Tiantian Ren (Institute of Advanced Engineering and Science, 2014)
Particle swarm optimization is introduced to solve the problem in this paper. Instead of solving a group of non-linear equations, forward kinematics is solved by computing the extrenum of a function. And accurate solutions can be obtained by the global and local searching abilities of advanced particle swarm optimization. It overcomes the shortage that precision is greatly influenced by initial values with conventional numerical methods. Calculation results show that this new method is simple, convenient, and with generality for solving the parallel manipulator forward kinematics problems.